ANALYSIS OF FACTORS AFFECTING THE USE OF ACCOUNTING INFORMATION IN MICRO, SMALL, AND MEDIUM ENTERPRISES IN MATARAM - Yuhana Nurhandayani; Ida Ayu Nursanty; Elvina Setiawati (ShariaBiz International Journal of Economics & Business, 2024)
This study aims to analyze the factors that influence the use of accounting information on Micro, Small, and Medium Enterprises in Mataram City. This study consists of two independent variables, namely business turnover (X1) and accounting knowledge (X2 ), and the dependent variable is the use of accounting information (Y). The population in this study is food and beverage MSMEs in the city of Mataram, amounting to 1,254 MSMEs. The sample selection method used in this research is the purposive sampling method. The criteria are based on the food and beverage MSMEs involved in using accounting information. The sample that meets the requirements in this study is 100 SMEs. The data analysis methods used are validity test, reliability test, multiple linear regression analysis, coefficient of determination, and hypothesis testing. Data analysis techniques using the Validity Test, Reliability Test, Classical Assumption Test, Normality Test, Multicollinearity Test, Heteroscedasticity Test, and Multiple Linear Regression Analysis. The results of this study indicate that the business turnover variable has no significant effect on the use of accounting information because it has a significance value level (Sig.) of 0.822 > 0.05 and a t-table of 1.660. accounting knowledge has no significant effect on the use of accounting information because it has a significance value level (Sig.) of 0.492 > 0.05 and t-count 0.690 < t-table 1.660 in food and beverage SMEs.